2009
DOI: 10.1017/s1743921309992936
|View full text |Cite
|
Sign up to set email alerts
|

Observation of non-Gaussianity and phase synchronization in intermittent magnetic field turbulence in the solar-terrestrial environment

Abstract: Abstract. We apply two nonlinear techniques, kurtosis and phase coherence index, to analyze magnetic field measurements from SOHO MDI solar images, ACE and Cluster data in the solar wind, and ground magnetometers in Brazil. We focus on two events: a non-ICME event in February 2002 and an ICME event in January 2005. Finite degree of non-Gaussianity and phase synchronization are observed in all datasets. The nonlinear response of the Earth's geomagnetic field to an ICME event in the solar wind is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…In the particular scenario of decimetric solar bursts, inhomogeneous plasma turbulence is possibly associated to the coronal plasma configuration where the radio burst is generated. It has been shown that when a X-class flare occurs, and there is a CME structurally associated, the interplanetary magnetic field turbulence downstream of the interplanetary CME shock is closely correlated with the geomagnetic turbulence (Sun et al, 2002;Miranda et al, 2009). Possibly, such interconnected event occurrence is due to the solar-terrestrial magnetic field coupling and to the intrinsic long-range correlation of the magnetic filament turbulence.…”
Section: Physical Interpretationmentioning
confidence: 99%
“…In the particular scenario of decimetric solar bursts, inhomogeneous plasma turbulence is possibly associated to the coronal plasma configuration where the radio burst is generated. It has been shown that when a X-class flare occurs, and there is a CME structurally associated, the interplanetary magnetic field turbulence downstream of the interplanetary CME shock is closely correlated with the geomagnetic turbulence (Sun et al, 2002;Miranda et al, 2009). Possibly, such interconnected event occurrence is due to the solar-terrestrial magnetic field coupling and to the intrinsic long-range correlation of the magnetic filament turbulence.…”
Section: Physical Interpretationmentioning
confidence: 99%